Digitalization of Logistics, Environmental Awareness, and Green Logistics Practices in Reducing Carbon Emissions in Retail Product Distribution within the Surakarta Urban Area - Noviana Puspitasari; Shinta Mardiana Dewi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of Logistics Digitalization, Environmental Awareness, and Green Logistics Practices on Carbon Emission Reduction in the retail product distribution sector in Surakarta City. A quantitative explanatory approach was employed by distributing structured questionnaires to 205 respondents, consisting of logistics actors, distribution managers, and retail operational staff. Data were analyzed using multiple linear regression through SPSS version 26 software. The findings reveal that all three independent variables have a positive and significant effect on carbon emission reduction, with a determination coefficient (R²) of 0.428. The Green Logistics Practices variable exerts the most dominant influence through the implementation of energy efficiency, distribution route optimization, and the use of low-emission vehicles. Logistics Digitalization contributes to operational efficiency enhancement through the utilization of Internet of Things (IoT) technologies, Big Data Analytics, and smart routing systems. Meanwhile, Environmental Awareness strengthens environmentally responsible organizational behavior and supports carbon-friendly decision-making. These findings reinforce the eco-efficiency theory, asserting that operational efficiency and environmental sustainability can progress simultaneously. The study highlights the importance of synergy between digital technology, ecological awareness, and green logistics practices as an effective strategy toward a low-carbon retail distribution system in Indonesia.